UR_GERICHTE 2016_OG S 16 9. vom 8. November 2016 - UR Obergericht (2016)
Strafprozessordnung. Art. 386 Abs. 2 lit. a, Art. 386 Abs. 2 lit. b, Art. 399 Abs. 3, Art. 428 Abs. 1 StPO. Art. 6 Gerichtsgebührenverordnung.